India - Living Conditions and Human Development in Uttar Pradesh : A Regional Perspective - World Bank (Washington, DC, 2013)
Uttar Pradesh, the largest state in India, has 170 million inhabitants who represent 16.2 percent of India's population. Uttar Pradesh (UP) is classified as one of the 'lagging states of India' for its slow growth, low human development indicators and high concentration of the poor. UP occupies an important position in India because of its size and as a determinant of the country's overall progress. UP has continuously slipped behind India as a whole. Growth or the lack of it has a mirror image in poverty trends. In the 1970s, UP's poverty level was almost at the national average and actually came below the all-India level in 1977-78. Poverty climbed again in 1983. Since the 1990s, slow growth in industry and services has been responsible for UP's lag. The report is organized as: it starts with an assessment of trends in growth, poverty, and inequality presents in chapter one. It notes a slower reduction in poverty in urban areas and in the Western and Eastern regions. Chapter two presents a poverty profile, its non-income dimensions and silent features of the dynamics of poverty. Chapter three presents the underpinnings of growth and reduction in poverty, the report examines patterns of employment, wages and migration patterns in UP. Chapter four focuses on the latent potential of the agricultural sector. Chapters five and six examine trends, challenges and achievements in education and health indicators. Chapter seven addresses access to social assistance programs. Chapter eight presents possible solutions for improving delivery of services.